Molecular Docking Study of Ageratum conyzoides-Derived Compounds Against the Human Cathepsin G–EapH1 Complex of Staphylococcus aureus: Molecular Docking Study of Ageratum conyzoides-Derived Compounds Against the Human Cathepsin G–EapH1 Complex of Staphylococcus aureus - Intan Tsamrotul; Dwina Ramadhani Pomalingo; Nur Afni Syariah Nasar (PharmaCine : Journal of Pharmacy, Medical and Health Science, 2026)
Under normal physiological conditions, neutrophils circulate throughout the bloodstream in a resting or quiescent state. However, following activation and the phagocytic uptake of opsonized bacterial pathogens, these cells experience substantial functional and physiological alterations that enhance their antimicrobial capabilities. Ageratum conyzoides is a medicinal plant reported to possess antimicrobial activity due to the presence of several bioactive phytochemicals. These compounds may serve as potential candidates for inhibiting bacterial virulence proteins. In addition to having a variety of beneficial biological activities, this compound also has some weaknesses. One of its main weaknesses is its low solubility in water, which can inhibit its bioavailability when consumed. Therefore, molecular docking of the compound Bandotan derivatives was carried out to address these weaknesses. The purpose of this study is to analyze the interaction of the Bandotan compound with the Human Cathepsin-G Inhibited by S. aureus Eaph1 receptor (6VTM); Molecular docking was performed using AutoDockTools 1.5.7, while the absorption, distribution, metabolism, and excretion properties of the compounds were predicted using the pkCSM web server, and their toxicity was evaluated using the ProTox-II web server. The ligand–receptor interactions were visualized using BIOVIA Discovery Studio Visualizer. All compounds derived from Ageratum conyzoides were able to interact with the human cathepsin G–EapH1 complex of S. aureus (PDB ID: 6VTM). Sesamin exhibited the most favorable binding energy of −6.21 kcal/mol, with an estimated inhibition constant (Ki) of 28.22 µM. The compound interacted with Arg977, Asp974, Pro975, Ile981, Asp984, Val980, Gly983, Gln976, Leu979, Glu985, and Gln982 through hydrogen bonds and other noncovalent interactions. Overall, sesamin demonstrated the best docking performance among the evaluated compounds and was identified as the most promising A. conyzoides-derived compound for interaction with the human cathepsin G–EapH1 complex.